Numerics of Unilateral Contacts and Friction Modeling and Numerical Time Integration in Non-Smooth Dynamics - Studer, Christian (Lecture Notes in Applied and Computational Mechanics, 2009)
This book is especially suited for people both in research and industry who are interested in the numerical simulation of mechanical systems with unilateral contacts and friction. Such systems can be found in various fields of technical application; consider for example contacts between wheels and ground in vehicle dynamics, walking machines, limit stops and friction in arbitrary kind of mechanisms or contacts between thousands of grains in granular mechanics. The book focuses mainly on rigid multibody systems dynamics with unilateral contacts and friction, however, the proposed non-smooth modeling approach is much more general and also well suited for non-rigid applications. Four main topics are addressed: Non-smooth modeling of unilateral contacts and friction by set valued force laws, Mathematical evaluation of these laws using normal cone inclusions with associated projective equations, Numerical time-stepping integration methods for non-smooth systems, Implementation in a software code. The book closes the gap between highly specialized mathematical literature and engineering application, gives an excellent overview on well established methods in non-smooth mechanics and opens new perspectives for the future development in this promising field of active research.